Business game as a pedagogical tool for developing students’ global competencies - Vera M. Zhurakovskaya; Olga A. Olicheva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
One of the important tasks of implementing state educational policy is the quality of education, expressed in functional literacy, which also includes the global competencies of students. The paper raises the problem of developing pedagogical tools and conditions that determine the development of global competencies of secondary school students. The aim of the paper is to develop the structure of a business game that determines the development of global competencies of secondary school students, to describe the practical application of the structure of a business game when designing specific business games in the educational practice of a secondary school. The study proposes a new structure of a business game and offers an example of the business game “BRICS Summit”, designed on the basis of this structure. The scientific novelty of the research includes the development of a business game designed on the basis of the integration of scientific approaches: synergetic, activity-based, coaching, the interpenetration of which determined the development of new structural components of a business game focused on the formation of global competencies of students. The theoretical significance of the study was the theoretical principles underlying the structure of the business game, which will contribute to the expansion and enrichment of the theory of design of pedagogical technologies that determine the formation of global competencies of students, and will require the conduct of business games for students in extracurricular activities in the educational process. The practical significance of the study is in practical application of the structure of a business game in the professional activities of a teacher when designing business games as extracurricular activities that determine the formation of global competencies of students. Analysis of business games implementation in an educational organization in extracurricular activities, which determine the formation of students’ global competencies, made it possible to identify the positive dynamics of the development of students’ experience of global thinking and, on this basis, to substantiate the effectiveness of the designed pedagogical tools.